Influencer Marketing Revolutionizes Culinary Businesses Globally: Influencer Marketing Merevolusi Bisnis Kuliner Secara Global - Rosyid V. M, Mufti; Sampurno, Feri D.; Arief, Mochamad Fahmy; Mardhiyah, Siti; Rahmawati, Imelda Dian (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the impact of influencer marketing on culinary businesses, focusing on Padang Payakumbuah restaurant. Through a literature study approach, it investigates influencer marketing's role in brand promotion, exposure, and consumer response. Data collection involves academic journals and social media platforms like Instagram and TikTok. Results reveal that influencer marketing significantly enhances brand image and engagement. Padang Payakumbuah's success in influencer collaborations emphasizes the importance of aligning influencers with brand identity. Overall, this research highlights influencer marketing's crucial role in digital marketing for culinary businesses, providing insights for marketers to effectively engage consumers and strengthen brand promotion. Highlights: Enhanced Brand Image: Influencer marketing boosts brand image for culinary businesses. Aligned Brand Identity: Successful collaborations align influencers with brand identity. Effective Consumer Engagement: Insights for marketers to engage consumers in digital marketing. Keywords: Influencer Marketing, Culinary Businesses, Brand Promotion, Digital Marketing, Consumer Engagement